2021
DOI: 10.18502/acta.v59i8.7248
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Risk Factors Associated With Mortality Among Patients With COVID-19 Using Random Forest Model: A Historical Cohort Study

Abstract: There is conflicting evidence about factors associated with Clinical course and risk factors for mortality of adult inpatients. We aimed to identify the demographic, clinical, treatment, and laboratory data factors associated with mortality in the Khoy district. We performed a retrospective cohort study including COVID-19 infected patients who were admitted to Qamar-Bani Hashim hospital from 2 November 2020 to 4 December 2020. We used random forest methods to explore the risk factors associated with death. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Up to the date of April 30, 2020, more than three million confirmed cases and 208000 deaths had been reported from 213 countries (1). Du et al, have shown factors such as old age, cardiovascular or cerebrovascular diseases, low lymphocyte count, and high cardiac troponin I as predictors of mortality among these patients (2,3). Other studies have emphasized the impact of comorbidities on patient outcomes (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Up to the date of April 30, 2020, more than three million confirmed cases and 208000 deaths had been reported from 213 countries (1). Du et al, have shown factors such as old age, cardiovascular or cerebrovascular diseases, low lymphocyte count, and high cardiac troponin I as predictors of mortality among these patients (2,3). Other studies have emphasized the impact of comorbidities on patient outcomes (4,5).…”
Section: Introductionmentioning
confidence: 99%